Fatigue failure study of fiberglass sucker rods joints - Kopej, Bogdan Volodimirovič; Bednarz, Stanisław; Shuanjui, Youy (My University, 2016)
Fiberglass sucker rods are fiberglass rods (body) of polymeric composite materials (PCM), which are connected with steel heads. In this paper, an analysis of the fatigue strength of joints of fiberglass sucker rod under different bending stresses is performed and from this the key indicators of fatigue strength are derived. The main scope of fiberglass sucker rod is the use in aggressive environment because the plastic and glass fiber is not exposed to corrosion. Long-term strength and durability of operation – it’s the most important characteristics used in the design and operation realized in sucker rod, made of polymer composite materials (PCM). The aging of polymers and fiberglass sucker rod fracture leads to an emergency in the operation of oil wells and need to execute the workover. Based on the found contact problem solving using computers strength characteristics of the compounds were analyzed, dependence of contact pressure on the value of shear compliances of shell material, orthotropy option, size of joint were obtained.
AGH Drilling, Oil, Gas
Keywords: fiberglass; sucker rod; steel head; bending stress; fatigue strength